Dysregulated expression of microRNA-150 in human papillomavirus-induced lesions of K14-HPV16 transgenic mice - Joana M. O. Santos (2017)
Aims: High-risk human papillomavirus (HPV) infection is one of the major causes of infection-related cancers worldwide. MicroRNAs (miRNAs) are a family of non-coding RNAs (ncRNAs), whose dysregulated levels may cause an aberrant expression of genes involved in oncogenic pathways and consequently lead to cancer development. This is the case of the miRNA-150 (miR-150), whose expression in HPV-induced lesions remains unclear and the present work aims to clarify it. We employed K14-HPV16 mice, which express the early genes of HPV16 in basal keratinocytes, leading to the development of hyperplastic and dysplastic skin lesions and squamous cell carcinomas, and are a representative model of HPV-induced cancers. Main methods: In order to evaluate the expression of miR-150 in HPV-induced lesions, we performed qPCR in wild-type mice (HPV−/−) and in skin lesions of K14-HPV16 transgenic mice (HPV+/−). Matched skin samples were analyzed histologically. Key findings: 24-26 weeks-old HPV+/− mice showed diffuse epidermal hyperplasia and focal dysplasia in a hyperplastic background (31.8% incidence), but 28-30 weeks-old HPV+/− mice presented higher incidence of dysplasia (100.0%). MiR-150 was upregulated in HPV+/− mice when compared with HPV−/− mice (p b 0.001). MiR150 was also overexpressed in diffuse dysplastic lesions when compared with hyperplastic lesions (p = 0.005). Significance: The present results suggest that miR-150 is overexpressed in HPV-induced lesions in this model and its expression seems to increase with lesion progression, along the process of multi-step carcinogenesis.